Physical Capabilities of Syiah Kuala University's Pencak Silat UKM Athletes in 2024 - Putra, Sukardi; Abdurrahman, Abdurrahman; Iqbal, Muhammad; Zahara, Zahara; Isdarianti, Novi Lidya; Fikry, T. Dhiyaul (Musamus Journal of Physical Education and Sport (MJPES), 2024)
Objective. The analysis of the coach's response indicates a deficiency in physical capability during the match, particularly in the execution of punches and kicks that lack sufficient strength. This investigation aims to assess the physical capabilities of UKM Pencak Silat USK athletes in 2024. Materials and Methods. The approach utilises quantitative methods. Descriptive research methodology. The study focuses on the athletes of UKM Pencak Silat USK in 2024, comprising a total of 24 individuals. The process of data collection involved assessing various physical attributes, including Leg Strength through a leg dynamometer, Arm Strength via push-ups, Endurance measured by a 12-minute run, Flexibility assessed through the sit and reach test, Speed evaluated with the hexagonal obstacle test, Coordination tested with the hand wall toss test, Agility determined by the shuttle run, Leg Muscle Explosive Power through vertical jumps, and Arm Muscle Explosive Power via pull-ups. Results. Data is analysed through statistical tests, focusing on the average values and percentage distributions of various physical conditions among male and female athletes. The assessment of Leg Strength (Leg dynamometer) indicates that both genders fall within the Less category. In terms of Arm Strength (Push Up), both male and female athletes are classified in the “Good” category. For Endurance (Running 12 minutes), male athletes are categorised as “Less,” while female athletes are in the “Very less” category. The evaluation of Flexibility (Sit and Reach) shows male athletes in the “Enough” category and female athletes in the “Good” category. Lastly, the Speed (Hexagonal Obstacle Test) results place both male and female athletes in the “Moderate” category. The physical condition percentage for Coordination (Hand Wall Toss Test) indicates that male athletes fall into the "Good" category, while female athletes are classified as "Moderate." For Agility (Shuttle Run), both male and female athletes are categorised as "Moderate." In terms of Leg Muscle Explosive Power (Vertical Jump), both groups are rated as "Enough." However, the percentage for Arm Muscle Explosive Power (Pull Up) shows that both male and female athletes are in the "Poor" category. Conclusion. The findings of the study indicate that the physical condition of male and female athletes of UKM Pencak Silat USK in 2024 is primarily categorised as Less.